Performance Study of Dynamic Source Routing Protocol with respect to Mobility of Ad hoc network - Nikam, Samiksha; Jadhav, BT (International Journal of Computer Sciences and Engineering, 2022)
Ad hoc network is a collection of mobile nodes that dynamically form a temporary network. This network is self-organized and does not have any centralized control. Each node acts as a router. In ad hoc network, nodes are independent of each other and free to move anywhere which changes topology dynamically. Therefore, routing is one of the centralized requirements in such type of network. In this paper DSR routing protocol is studied. The performance of routing protocol is affected by the network scenario parameters like Pause time, number of nodes, Speed of nodes and number of connectors between the nodes. The performance analysis of the protocols is the most important step prior to selecting a particular protocol. In real world scenario pause time and speed of nodes frequently changes. This paper analyses performance of DSR protocol using network simulator ns2.34 in high and low pause time scenario. The performance of DSR protocols has been evaluated on the basis of average throughput, delay, Packet delivery fraction (PDF), and Normalized Routing Load (NRL) metrics. The simulation results show that DSR protocol work efficiently in low mobility scenario. When node mobility increases performance degrades. We believe that this study will give comprehensive analysis of DSR protocol under low and high mobility scenario, which will help researchers further to investigate any metric for particular protocol.